ANALISIS HUKUM TERHADAP PENANGGUHAN PENAHANAN (Studi Pada Kepolisian Resor Banggai) - Mamu Pati, Herman Yoseph; Jubair; Syachdin (Universitas Tadulako, 2024)
Although there have been limitations set forth in the national Criminal Procedure Code which have been adapted to the conditions or legal life of Indonesia, the Criminal Procedure Code itself is not free from shortcomings. The shortcomings contained in the Criminal Procedure Code have caused many new problems, including in terms of detention, namely the granting of a suspension of detention and the refusal to grant a suspension of detention, even though in statutory provisions it is the right of a suspect or defendant in every level of a criminal case. The problem that will be described in this study is how the implementation of the suspension of detention for suspects at the Banggai Resort Police and what are the reasons and constraints for granting a suspension of detention at the Banggai Resort Police. The purpose of the study was to determine and analyze the implementation of the suspension of detention of suspects at the Banggai Resort Police. To find out and analyze the practice of reasons and obstacles in granting a suspension of detention at the Banggai Resort Police. By using empirical juridical method. The implementation of the suspension of detention at the Banggai Resort Police has been carried out in accordance with the legislation (KUHAP) but has not been maximized as there are still some cases that should be given a detention suspension but are not granted and the obstacles faced by the Banggai Resort police in terms of suspension of detention include not getting permission from Even though the leadership is in accordance with the conditions for the suspension of detention in cases classified as severe, namely (Street Crime), many suspects who apply for a suspension of detention are recidivist perpetrators so that it is feared that the person concerned will repeat the crime, that there is attention from the police leadership at the regional police and headquarters related cases. street crime (street crime), drugs, stealing, stealing and maltreatment which are very disturbing to the public regarding the murder case, the request for suspension is not granted because it is to prevent new problems such as revenge from the victim's family from arising. trigger new criminal acts